Decolonial curatorial practices in dialogue (Palíndromo, 2022)
This paper seeks to reflect about curatorial procedures resulting from recent discussions and revisions in the history of art, as well as in museum collections. In order to contextualize the reflections on these practices, the theoretical basis establishes discussions with authors such as Ivan Muñiz-Reed, Lucy Lippard, Tomislav Šola, among others. It analyzes interviews carried out by the authors of this paper with Brazilian curators Carollina Lauriano, Igor Simões, Luciara Ribeiro and Pollyana Quintella, considering a decolonial turn in progress. Different practices and approaches are presented in which curatorship and theoretical research assume activist positions and recover the names and works by historically discriminated and rejected artists. When studying different strategies and perspectives, a panorama of possibilities is outlined in which we can analyze what has already been done, recognize what is under construction and project futures.
Keywords: Curatorship; Art History; Exhibition; Activism; Decoloniality